Staying Alert? Neural Correlates of the Association Between Grit and Attention Networks - Kalia, Vrinda; Thomas, Robin; Osowski, Kira; Drew, Anthony (Frontiers in Psychology, 2018)
Recent research has demonstrated that heightened motivational levels promote enhanced attention capabilities. However, the relation between attentional systems and the trait-based ability to sustain a motivational state long-term is less understood. Grit refers to one’s ability and willingness to pursue long-term goals despite setbacks. This report presents the results of two studies conducted to examine the relation between facets of Grit – Consistency and Perseverance and attention networks, assessed using the Attention Network Test (ANT). Across both studies Grit – Perseverance was related to performance on the ANT. In Study 1, Grit – Perseverance was negatively related to alerting indicating that individuals who were high on Perseverance were more likely to show a smaller alerting effect. In particular, Grit – Perseverance was negatively correlated with reaction times in the no cue trials. In Study 2, we assessed ERP components associated with attention networks. Individuals with higher scores on Grit – Perseverance were more likely to demonstrate smaller mean difference in N1 amplitudes for double cue relative to no cue trials, suggesting an attenuated alerting effect. Our findings indicate that individuals high on Grit – Perseverance may have enhanced sustained attention. Gritty individuals may be intrinsically motivated and less sensitive to new information in their attention field. Implications of high levels of Grit on cognitive performance are discussed.